Functional Status Score for the ICU: An International Clinimetric Analysis of Validity, Responsiveness, and Minimal Important Difference. Issue 12 (December 2016) - Huang, Minxuan; Chan, Kitty S.; Zanni, Jennifer M.; Parry, Selina M.; Neto, Saint-Clair G. B.; Neto, Jose A. A.; da Silva, Vinicius Z. M.; Kho, Michelle E.; Needham, Dale M.
Abstract : Objectives: To evaluate the internal consistency, validity, responsiveness, and minimal important difference of the Functional Status Score for the ICU, a physical function measure designed for the ICU. Design: Clinimetric analysis. Settings: Five international datasets from the United States, Australia, and Brazil. Patients: Eight hundred nineteen ICU patients. Intervention: None. Measurements and Main Results: Clinimetric analyses were initially conducted separately for each data source and time point to examine generalizability of findings, with pooled analyses performed thereafter to increase power of analyses. The Functional Status Score for the ICU demonstrated good to excellent internal consistency. There was good convergent and discriminant validity, with significant and positive correlations ( r = 0.30–0.95) between Functional Status Score for the ICU and other physical function measures, and generally weaker correlations with nonphysical measures (| r | = 0.01–0.70). Known group validity was demonstrated by significantly higher Functional Status Score for the ICU scores among patients without ICU-acquired weakness (Medical Research Council sum score, ≥ 48 vs < 48) and with hospital discharge to home (vs healthcare facility). Functional Status Score for the ICU at ICU discharge predicted post-ICU hospital length of stay and discharge location. Responsiveness was supported via increased Functional Status Score for the ICU scores with improvements in muscle strength. Distribution-based methods indicated a minimal important difference of 2.0–5.0. Conclusions: The Functional Status Score for the ICU has good internal consistency and is a valid and responsive measure of physical function for ICU patients. The estimated minimal important difference can be used in sample size calculations and in interpreting studies comparing the physical function of groups of ICU patients. Abstract : Supplemental Digital Content is available in the text.